THE ROLE OF PUBLIC RELATIONS IN IMPROVING THE POSITIVE IMAGE OF THE POLICE INSTITUTION IN THE WEST SUMATERA REGIONAL POLICE - Yulianti, Tri Dewi; Eliza, Yulin; Putra, Elsandra Eka; Andria, Yass (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The purpose of this study is to ascertain how public relations contributes to the West Sumatera Regional Police's improved perception of itself as a police force. The West Sumatra Regional Police's Public Relations Division carried out this qualitative descriptive study. The West Sumatra Regional Police's Head of Public Relations and Head of the Information and Documentation Management Sub-Division (KasubbidPID) served as the study's research subjects. The data analysis approach used is the data triangulation methodology, which entails steps of data reduction, data display, and conclusion drafting. The results of the study show that public relations, by carrying out its main responsibilities under the supervision of yearly, monthly, and weekly activity plans in addition to a daily schedule, plays a critical role in improving the positive perception of the West Sumatra Regional Police. In order to provide the public with timely, accurate, and dependable information about the positive actions taken by West Sumatra Regional Police members, Public Relations of the West Sumatra Regional Police disseminates information about the various activities that the police have carried out through internal media as well as local and national media. The public will see the National Police in a more favorable light as a result. 2) The inability of West Sumatra Regional Police members to publicly acknowledge their work as law enforcement officers is one of the barriers to the organization's efforts to cultivate a more positive public image. Furthermore, internet signal service is still unavailable in a large number of West Sumatra locations. As a result, the residents of these places are unaware of the status of the different operations being conducted by the West Sumatra Regional Police. In addition, public relations attempts to enhance the National Police's favorable reputation are hampered by delays in providing information to the public. In addition, the public's unfavorable opinion of the National Police organization is one more barrier to public relations that the West Sumatra Regional Police faces and has to be resolved right away to preserve the National Police's good reputation. 3) The activity plans that have been established will serve as a guide for West Sumatra Regional Police Public Relations' efforts to overcome barriers to enhancing the favorable image of the National Police. Additionally, the department will cultivate relationships with both local and national media and motivate officers to actively engage in publicizing activities. his great actions on his own social media as a police officer.